PESQUISA DE SATISFAÇÃO EM FEIRAS: UM OLHAR CRÍTICO SOBRE A 17ª FENASOJA - Wagner, Adriano; Sparemberger, Ariosto; Battisti, Iara D. E.; Zamberlan, Luciano; Buttenbender, Pedro L. (Salão do Conhecimento, 2013)
Resumo